Interferon-γ release assay screening in biologics: safe and reliable, but not perfect. Issue 4 (28th November 2022) - Cafferkey, John; Padayachee, Yorissa; Kostich, Sophia; Kumar, Kartik; Jewell, Paul; Patel, Mikin; Chavda, Aneeka; Cox, Alison; Park, Mirae; Russell, Georgina; Coleman, Meg; Martin, Laura; et al.
Background: Systemic biologic agents can increase the risk of re-activation of latent tuberculosis (TB). Prior to initiation, screening for latent TB using an interferon-γ release assay (IGRA) is recommended. There is concern that false-negative IGRAs may be more likely in this context. Methods: This retrospective analysis of IGRAs, specifically T-SPOT.TB, results and outcomes of patients already on or due to start biologics identifies the rate of TB re-activation in a low TB incidence setting. Additionally, we estimate the negative predictive value (NPV) of IGRAs in this population. Results: Patients on biologics were more likely to have a negative IGRA result than patients not on biologics. There was no statistically significant change in conversion or reversion rates between groups. Of 9263 patients on biologics, 19 developed active TB after starting biologics at an incidence rate of 55.1 per 100 000 patient-years. This occurred despite screening in half of the 16 patients for whom we were able to review medical records. Most drugs implicated were known to be high risk, although rituximab and natalizumab were being taken by five patients and one patient, respectively. The T-SPOT.TB NPV was 99.20% and dropped only slightly to 99.17% when we simulated an approach where all borderline IGRA results were regarded as being negative. Conclusions: Negative IGRA results confer a low risk of subsequent active TB in patients on biologics in a low TB incidence setting. However, continued awareness is needed given that a number of active TB cases will have had a prior negative result. This retrospective analysis examines TB outcomes and IGRA performance in a large cohort of patients on biologics. It signals that negative and even borderline IGRA results confer a low risk of subsequent active TB in patients on biologics. https://bit.ly/3T9rlQ7